A new species of Charadrahyla (Anura: Hylidae) from the cloud forest of western Oaxaca, Mexico - Jiménez-Arcos, Víctor H.; Calzada-Arciniega, Rafael Alejandro; Alfaro-Juantorena, Liz A.; Vázquez-Reyes, Leopoldo D.; Blair, Christopher; Parra-Olea, Gabriela (Zootaxa, 2019)
A new species of treefrog from the genus Charadrahyla is described from the cloud forest of western Sierra Madre del Sur of Oaxaca, Mexico. Charadrahyla sakbah sp. nov., is distinguished from the rest of the species in the genus by the large body size (81.15–85.75 mm and 67.91–73.21 mm in adult females and males respectively), axillary membrane, adult males with hypertrophied webbings between toes I and II, nuptial excrescences, one enlarged conical tubercle on either side of vent, vocal slits absent, and sexual dimorphism in the snout shape in dorsal profile (rounded and acuminate in females and males respectively). The hypertrophied webbings are a unique character among other hylids of Middle America, and are only present in C. trux, C. tecuani and the species described herein. These three species inhabit the cloud forest of the Sierra Madre del Sur, and are probably closely related. However, more detailed phylogenetic analyses are needed to define the internal relationships of the genus. The cloud forest in the Sierra Madre del Sur continues to be known for a high number of endemic species. However, the cloud forest faces several threats due to its limited distribution that make it a priority ecosystem for conservation.